A universal formula for the relativistic correction to the mutual friction coupling time-scale in neutron stars. Issue 3 (7th April 2020) - Gavassino, L; Antonelli, M; Pizzochero, P M; Haskell, B
ABSTRACT: Vortex-mediated mutual friction governs the coupling between the superfluid and normal components in neutron star interiors. By, for example, comparing precise timing observations of pulsar glitches with theoretical predictions it is possible to constrain the physics in the interior of the star, but to do so an accurate model of the mutual friction coupling in general relativity is needed. We derive such a model directly from Carter's multifluid formalism, and study the vortex structure and coupling time-scale between the components in a relativistic star. We calculate how general relativity modifies the shape and the density of the quantized vortices and show that, in the quasi-Schwarzschild coordinates, they can be approximated as straight lines for realistic neutron star configurations. Finally, we present a simple universal formula (given as a function of the stellar compactness alone) for the relativistic correction to the glitch rise-time, which is valid under the assumption that the superfluid reservoir is in a thin shell in the crust or in the outer core. This universal relation can be easily employed to correct, a posteriori, any Newtonian estimate for the coupling time-scale, without any additional computational expense.